2021
DOI: 10.1007/s00405-021-06842-1
|View full text |Cite
|
Sign up to set email alerts
|

Sound localization with bilateral bone conduction devices

Abstract: Purpose To investigate sound localization in patients bilaterally fitted with bone conduction devices (BCDs). Additionally, clinically applicable methods to improve localization accuracy were explored. Methods Fifteen adults with bilaterally fitted percutaneous BCDs were included. At baseline, sound localization, (un)aided pure-tone thresholds, device use, speech, spatial and qualities of hearing scale (SSQ) and York hearing-related quality of life (YHRQL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Chin et al (2021) also demonstrated better hearing threshold, speech reception thresholds in noise and directional hearing with bilateral simultaneous implantation with the tBCHD Bonebridge devices [25]. Similarly, Caspers et al (2022) studied the efficacy of bilateral implantation with pBCHDs on sound localization [26]. Heath et al (2021) published a systematic review to assess the outcomes of bilaterally fitted patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chin et al (2021) also demonstrated better hearing threshold, speech reception thresholds in noise and directional hearing with bilateral simultaneous implantation with the tBCHD Bonebridge devices [25]. Similarly, Caspers et al (2022) studied the efficacy of bilateral implantation with pBCHDs on sound localization [26]. Heath et al (2021) published a systematic review to assess the outcomes of bilaterally fitted patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dun and coauthors reported a score of 5.8 in the spatial scale of the SSQ49 for bilaterally fitted children. Caspers et al (2022 ) also collected SSQ scores on bilaterally implanted BAHS users (adults) but the data were not reported. Other studies ( Kunst et al 2008 ; Bosman et al 2018 ; Cuda et al 2021 ; Bosman et al 2021 ) collected SSQ49 scores using a group of adult users—most of which were unilaterally implanted.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al (2017) [41] described that the difference between premiumfeature hearing aids (i.e., with multi-channel adaptive DMs, pinna effect simulation, and an advanced synchronization function) and basic-feature hearing aids (i.e., with singlechannel adaptive DMs and a basic synchronization function) was not significant in selfreported everyday sound localization. Caspers et al (2021) [29] switched off adaptive DM and noise reduction in the setting of BCDs to avoid deterioration in localization performance.…”
Section: Devicesmentioning
confidence: 99%
“…They stated that the difference must be caused by late-development brain plasticity for binaural hearing. Caspers et al (2021) [29] reported that bilaterally fitted patients with bilaterally acquired hearing loss, as well as patients with congenital hearing loss, were capable of localizing sounds (quite) accurately. For the obtained bilateral BC thresholds, they described that sound lateralization was more accurate in patients with symmetric and near-normal BC thresholds when compared with patients with either asymmetric BC thresholds or patients with BC thresholds of 25 dB and higher, and that normal symmetric thresholds did not warrant good localization.…”
Section: Patients With Bilateral Chlmentioning
confidence: 99%
See 1 more Smart Citation